STRATEGI PENGEMBANGAN KOMUNIKASI MASYARAKAT KELOMPOK TANI QORYAH TOYYIBAH DI KALIBENING KECAMATAN TINGKIR KOTA SALATIGA - Ilyas Ilyas (IAIN Salatiga, 2016)
This research was aimed to reveal strategy of society communication development within Qoryah Thoyyibah farmer association, through the farmer effort to increase organic rice plant commodity. This research used descriptive qualitative approach and method where the data were collected through observation, interview, documentation, and it also used triangulation of resource, data, and theory. The research subjects were the member and the committee of Qoryah Toyyibah farmer association at Kalibening, Tingkir district of Salatiga city. Through society empowerment, farmer association of organic rice plant commodity economically has raised their welfare better through cooperatives system where it becomes the alternative activity in management especially about financial that involves farmer crop starting from planting process, maintenance process, up to crop yield management. Moreover, the strategy of society communication of farmer association was able to strengthen the friendship among the member by implementing Javanese culture philosophy, mutual assistance, friendly and peaceful communication in monthly meeting conducted. Abstrak Abstrak Penelitian bertujuan mengungkap strategi pengembangan komunikasi masyarakat Kelompok Tani Qoryah Toyyibah melalui usaha para petani untuk meningkatkan komoditas tanaman padi organik. Metode yang digunakan kualitatif diskritif, melalui observasi, wawancara, dokumentasi, dengan menggunakan trianggulasi sumber, data, dan teori. Subjek telitinya adalah anggota dan pengurus kelompok tani Qoryah Toyyibah di Kalibening Kecamatan Tingkir Kota Salatiga. Melalui pemberdayaan masyarakat kelompok tani komoditas tanaman padi organik ini secara ekonomis meningkatkan kesejahteraan dengan hasil yang baik melalui sistem perkoperasian sebagai wadah aktifitas dalam manajemen terutama masalah keuangan. Berangkat dari proses menjelang penanaman, proses perawatan, sampai manajemen hasil panen, selain, strategi komunikasi masyarakat mampu mempererat tali silaturahim antaranggota, dengan selalu menjunjung tinggi nilai falsafah budaya Jawa, gotong royong, guyub, rukun dalam bentuk dan cara diadakannya pertemuan rutin bulanan.